Ethical pleasure, visual dzikir, and artistic subjectivity in contemporary Indonesia - George, Kenneth M. (Material religion, 2008)
Drawing from a long-term ethnographic collaboration with Indonesian painter A. D. Pirous, this article examines the mingling of art and religion for what it may tell us about subjectivity and the senses in a predominantly Muslim public culture. Recent statements describe subjectivity as the site of a social actor's sensibility, reflexivity, and judgment and as an annex to prevailing social, cultural, and ideological circumstances. Following some brief reflections about artistic and religious subjectivity, this essay discusses the Islamic revival in Indonesia since the 1970s, a revival that has given spirituality, and Sufism in particular, new popularity and appeal. It then turns to a set of artistic practices that Pirous associates with "ethical pleasure" and with dzikir, the "mindfulness of God" that Muslims, and Sufis in particular, are careful to cultivate. Subjectivity acquires artistic and religious dimension in these practices, particularly as the senses engage with paint and canvas in devotional-aesthetic acts of "visual dzikir." We see that the intermingling of aesthetic and religious ideologies in the reflexive, sensorial sphere of subjectivity is not an interior or ethnographically unavailable phenomenon, but one that is cultural and public, worked out in the sensuous materiality of things and the world of social discourse.